Deforestation Characteristics between 2006 and 2020 over Tropical Forest in Central Kalimantan, Indonesia - Segah, Hendrik; Afentina, Afentina; Fatkhurohman, Fatkhurohman; Aguswan, Yusuf (Indonesian Journal of Geography, 2025)
Deforestation is reported to possess a vast and detrimental impact on the environment, economy, and social aspects of the community. In this context, the phenomenon should be assessed and analyzed to inform the decision-maker overseeing issued policy and development strategies. Therefore, this research aimed to characterize deforestation in Central Kalimantan between 2006 – 2020 using land cover map issued by the Indonesian Ministry of Environment and Forestry. Changes in natural forest cover were calculated and analyzed using the Remote Sensing and Geographical Information System (GIS) to determine trend, location, and land cover replacement of deforestation, reforestation, and degradation in Central Kalimantan Province, Indonesia. A series of Landsat images from 2000 to 2020 was used with a spatial resolution (30 m) and frequent revisit cycles. Additionally, the levels of forest loss, restoration, and degradation were accurately mapped by analyzing spectral bands and vegetation indices, providing valuable information for conservation efforts and other land-based policies. The results showed that Central Kalimantan lost 1.5 million ha of natural forest with a rate of deforestation of 117,000 ha/year from 2006 to 2020. Deforestation showed a decreasing trend and fluctuation in secondary swamps and dry forests located in the southern part of the island. This research could be used as a base to determine the target location for rehabilitation strategy to prevent further deforestation.Received: 2023-10-23 Revised: 2024-01-11 Accepted:  2025-01-24 Published: 2025-02-12